Activity patterns in a feline assemblage in south-west Mexico, and their relationship with prey species. (6th September 2020) - Hernández-Sánchez, Alejandro; Santos-Moreno, Antonio
Abstract: Several species of neotropical felines are morphologically and ecologically similar, and are sympatric along large areas of their distribution. This requires mechanisms to allow their coexistence, such as temporal segregation of their activities. The aim of this study was to evaluate the relation between activity patterns of felines and their prey using camera trapping data and their seasonal variation in two tropical environments in south-western Mexico. Excepting Puma concolor, activity patterns for each feline species did not differ significantly between seasons nor between vegetation types. Activity patterns did not differ significantly between species of similar size: mid-sized species had high activity pattern overlaps in the medium forest while large-sized species overlapped to a lesser extent in the cloud forest. Leopardus wiedii differed from large-sized predators in its activity patterns. We recorded a relatively high temporal overlap between felines and their main prey species, particularly in the periods of maximum activity. We found no evidence of temporal segregation between the felines of the Sierra Norte region of Oaxaca and we suggest their coexistence is mediated by the selection of prey with different activity patterns.